Phloem and xylem modifications of Vitis vinifera stems in response to flavescence dorée phytoplasma infection. (16th December 2020) - Jelmini, Luca; Rizzoli, Attilio; Jermini, Mauro; Schumpp, Olivier; Conedera, Marco
Abstract: Anatomical modifications of xylem and phloem tissues of grapevine ( Vitis vinifera ) stems of shoots infected by the flavescence dorée phytoplasma (FDp) were first observed and described in the 1960s, but never quantified in detail. In this paper, we describe and quantify the impact of FDp on grapevine stem tissues, and relate it to the level of expression of symptoms and to cultivar‐specific FDp susceptibility. For this purpose, we measured and quantified the anatomical parameters of xylem and phloem tissues of a tolerant (Merlot) and a susceptible (Chardonnay) cultivar. For each cultivar, thin sections of eight shoots with symptoms from FDp‐infected grapevines, eight symptomless shoots from the same FDp‐infected grapevines, and eight symptomless shoots from symptomless grapevines (control) were compared. Results showed general inhibition of xylem growth and proliferation of phloem tissues (hyperplasia) with lack or irregular arrangement of the fibre‐sclereids in the axial phloem of the stems from shoots with symptoms, irrespective of the cultivar. Xylem vessels of infected Merlot shoots were partly occluded by tyloses and a higher number of smaller vessels were produced than in control plants. Thus, the anatomical responses confirmed the detrimental effect of FDp on stems of infected grapevine shoots, including impaired stem development and lack of periderm formation. Statistically significant differences were found between the two cultivars with different levels of susceptibility to FDp infection. Abstract : Anatomical modifications in grapevines' stems due to flavescence dorée phytoplasma infection are measurable and significantly different between susceptible (e.g., Chardonnay) and tolerant (e.g., Merlot) cultivars.